STUDI DESKRIPTIF MINAT MAHASISWA STT KAO TENTANG PENGEMBANGAN KARUNIA ROH KUDUS DALAM PELAYANAN PEMBERITAAN INJIL - Luhur, Chandra Kirana (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
Carrying out the mission of the great commission is a general church task, which must be carried out by all believers. Conducting missions in the 4.0 era is a challenge in itself, and the university must empower the student with the gift of the Holy Spirit who can answer the needs of mission  services  in  this  era.  The research  is  a  quantitative  research, applying descriptive and phenomenological methods to show a description of service needs related to mission in the 4.0 era. As a result, a leader,must first be empowered in terms of gifts so as to optimize the gifts that are in the students.